Evaluation of bond strength of one step and two steps self-etch adhesive agents with two different pulp-capping materials - Rendžova Vasilka; Apostolska Sonja; Kostadinovska Emilija; Antanasova Maja; Eftimoska Marina; Petkov Marjan; Ristoska Stevica; Pavleska Meri (Serbian Medical Society - Dental Section, Belgrade, 2020)
Primary purpose of restorative dentistry is to preserve pulp vitality. Besides calcium hydroxide, the application of calcium silicate cements as a material for direct pulp capping has become used recently. The aim of our study was to investigate the influence of materials for direct and indirect pulp capping on the bond strength of composite restorations using two different self etch dentin adhesives. The test was performed on 60 intact molars extracted for periodontal or orthodontic reasons. The prepared samples were divided into the two groups and three subgroups depending on the adhesive and pulp cupping material. Two different calcium silicate based materials were used for pulp cupping. One step and two steps self etch dentin adhesive was applied to prepared specimens depending on the group and with the help of a specially made metal mold set up a composite post. The share bond strength was assessed using a universal testing machine. The results showed significant difference in the share bond strength between the samples treated with TheraCal LC and Biodentine with TheraCal LC being superior to Biodentine.